Taxes, leverage, and profit shifting in banks - Arthur José Cunha Bandeira de Mello Joia; Lucas Ayres B. de C. Barros; Marcelo Daniel Araujo Ermel (Economies, 2024)
The goal of this research is to investigate whether taxation affects the leverage decisions of banks and if the response of leverage to tax increases depends on profit-shifting opportunities available to individual banks. This topic remains controversial since it is often believed that banking regulation is such an essential driver of leverage choices that little room is left for other considerations studied in the corporate finance literature. Using a difference-in-differences setup encompassing the period from 2006 to 2017, we exploit two exogenous income tax rate increases applicable to 225 Brazilian banks, employing novel identification strategies based on the intricacies of local taxation rules and on the distinctions between individual banks and financial conglomerates. We find stark differences in the behavior of banks around the two events, with a substantial increase in leverage following the first tax hike but no leverage response following the second. In addition, we find no evidence of heterogeneous effects based on the amount of profit-shifting opportunities available to individual banks. Regulatory concerns possibly became more relevant for leverage decisions during the period around the second tax hike because it coincided with the implementation of stricter capital requirements associated with the Basel III framework. Taken together, our results suggest that financial institutions balance considerations regarding the tax-shield benefits of debt against regulatory concerns specific to the banking industry when making capital structure choices.
Keywords: 330; capital structure; bank regulation; corporate income taxation; trade-off theory; difference-in-differences; profit shifting